Czy muzyka jest ewolucyjną adaptacją? - Huron, David (Kultura-Społeczeństwo-Edukacja, 2015)
In this paper it is being argued that music might be regarded as a adaptive human behavior in the light of the evolutionary process. The author recalls here the NAPS theory of music according to which music does not prolong the existence of humanity but it might use one or many channels related to feeling pleasure which had evolved to strengthen adaptive behavior. The article recalls examples of theoreis of musical evolution connec ted to such issues as sexual choices, social integrity, development of perception, development of movement abilities, group effort, reduction of conf lict of interests, safe time consumption and communication between generations. All this evidence is being here regarded through archeological, anthropological and etological context. The conclusion of this paper is based on two assumptions. The first one is the notion that our mood is regulated through conversation and being with a friendly human. The other says that music takes and important place in this mood regulation.